Prenatal diagnosis of cloacal anomaly in trisomy 21 - Sweta Krishnan,; Aishwerya Singh, (Indian Journal of Case Reports, 2021)
The cloacal malformation is an extremely rare non-hereditary fetal anomaly that presents as a variety of defects. It predominantly affects females with a prevalence of 1 in 50,000 births. Here, we present the case of a 27-year-old primigravida at 32 weeks of gestation showing a large midline abdominopelvic cystic mass with a septum, bilateral hydroureteronephrosis with oligohydramnios in a female fetus on antenatal ultrasonography. Suspicion of the cloacal anomaly was made which was confirmed postnatally. Postpartum analysis of the placenta revealed trisomy 21.